Desain Majalah Penunjang Promosi Dan Informasi Pada AFC Indonesia - Andriyanto Andriyanto; Arfa Arfa; Virhaz Kurnia (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
The need for information to all areas is progressing so rapidly, many parties such as companies, institutions or organizations approach through forms of media print, film or electronic media. The approach of using the means of supporting the media performed in order to obtain the value of effectiveness in achieving the desired targets on a promotion that is used. As is the case at AFC Indonesia, a company that carries out functions and provide services. In order for the community or customer and are interested in purchasing products in Indonesia, the need for AFC media visual design process to help promote the company to the public. In accordance with the results of the interview, the company says that the current AFC Indonesia in disseminating and promoting the use of new banners, and billboards, yet also the existence of means of promotion that encapsulates the entire profile The company.